2016
DOI: 10.1002/jcb.25731
|View full text |Cite
|
Sign up to set email alerts
|

C/EBP‐β Is Differentially Affected by PPARα Agonists Fenofibric Acid and GW7647, But Does Not Change Apolipoprotein A‐I Production During ER‐Stress and Inflammation

Abstract: Increasing apolipoproteinA-I (apoA-I) production may be anti-atherogenic. Thus, there is a need to identify regulatory factors involved. Transcription of apoA-I involves peroxisome-proliferator-activated-receptor-alpha (PPARα) activation, but endoplasmic reticulum (ER) -stress and inflammation also influence apoA-I production. To unravel why PPARα agonist GW7647 increased apoA-I production compared to PPARα agonist fenofibric acid (FeAc) in human hepatocellular carcinoma (HepG2) and colorectal adenocarcinoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Indeed, Bai and coworkers have shown that overexpression of C/EBP-β increased the expression of cytokines such as IL-8 [ 28 ]. Furthermore, the ApoA-I promoter has a C/EBP binding site, which indicates that C/EBP-β might be involved in ApoA-I production [ 29 ]. As a result, we suggest in future experiments to investigate the role of SCFAs in rescuing the inflammation-induced reduction in ApoA-I expression by evaluating their effects on the C/EBP- β signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Bai and coworkers have shown that overexpression of C/EBP-β increased the expression of cytokines such as IL-8 [ 28 ]. Furthermore, the ApoA-I promoter has a C/EBP binding site, which indicates that C/EBP-β might be involved in ApoA-I production [ 29 ]. As a result, we suggest in future experiments to investigate the role of SCFAs in rescuing the inflammation-induced reduction in ApoA-I expression by evaluating their effects on the C/EBP- β signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated the mechanism of ICA attenuating diabetes-induced endothelial dysfunction through inhibiting ER stress. Activation of PPARα contributes to numerous pathologies by inhibiting ER stress, including diabetes (Chan et al, 2013;Ge et al, 2016), obesity , atherosclerosis (van der Krieken et al, 2017), and cardiovascular diseases (Huang et al, 2017). ICA has been implicated as the activator of PPARα in diabetes (Lu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein A1 (ApoA-I), the major protein component of HDL, has also been found to have anti-AS activity and to decrease the risk of CVDs [9]. Research has demonstrated the cardiovascular protective effect of ApoA-I by averting cholesterol accumulation in the vascular wall via the promotion of cholesterol efflux from the tissues to the liver for excretion [10].…”
Section: Introductionmentioning
confidence: 99%